Community Participation in Ecotourism Development Ir H Djuanda Forest Park - Ella Ayu Oktami; Tutut Sunarminto; Harnios Arief (Media Konservasi, 2018)
The existence of the Djuanda Forest Park near the urban area indirectly indicates that the area is close to the city community. The attitude of city people who tend to have an attitude of being able to take care of themselves without having to depend on others is feared to enter the surrounding communities and subsequently influence the development of Djuanda Tahura ecotourism. The research objective was to measure public perceptions of ecotourism and ecotourism objects in the Djuanda Forest Park, measuring community participation in the development of ecotourism in Djuanda Forest Park, and developing a strategy for increasing community participation in developing ecotourism in Djuanda Forest Park. The method used is observation, questionnaire, interview, and literature study. Communities strongly agree that ecotourism must meet indicators of community involvement, ecology, conservation, culture, education, and visitor satisfaction. The community considers that the Djuanda Tahura has beautiful ecotourism objects (highest average score = 4.61). The community values both ecotourism and the object of ecotourism because the community has a sense of care and sense of belonging to the Djuanda Tahura as an area that can provide benefits, both in ecological, social and economic aspects. However, community participation in ecotourism development is only in the implementation and acceptance of benefits and has participation in the form of personnel and expertise. Based on people's perceptions and participation, the community is at the lowest level of participation, so an SO strategy is needed, namely by utilizing all the strengths to make the most of opportunities. Keywords: Forest Park Ir H Djuanda, participation, perception, society, strategy